2010
DOI: 10.1183/09031936.00019210
|View full text |Cite
|
Sign up to set email alerts
|

Lung diseases directly associated with rheumatoid arthritis and their relationship to outcome

Abstract: The outcome and cause of death of each lung disease directly associated with rheumatoid arthritis (RA-LD) have been poorly investigated.A retrospective study was conducted of 144 patients with RA-LD, in whom the median follow-up period after the initial visit for a respiratory examination was 4.5 yrs.A total of 57 patients were identified with usual interstitial pneumonia (UIP), 31 with bronchiectasis, 16 with nonspecific interstitial pneumonia (NSIP), 11 with bronchiolitis, five with organising pneumonia (OP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
131
3
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 31 publications
7
131
3
14
Order By: Relevance
“…Chronic respiratory failure (as defined by the need of long-term oxygen therapy) occurred in 40% of patients, including four patients who died of respiratory failure [55]. In another series that evaluated 144 patients with rheumatoid arthritis and respiratory manifestations, 5-year survival rates were 36% in 57 patients with usual interstitial pneumonia, 87% in 31 patients with bronchiectasis, 94% in 16 patients with NSIP and 89% in 11 patients with bronchiolitis [83]. It is concluded that bronchiolitis is associated with poor prognosis essentially in patients with severe airflow limitation and marked hyperinflation, and that these features mostly occurred in patients with obliterative (rather than follicular) bronchiolitis.…”
Section: Rheumatoid Arthritismentioning
confidence: 98%
“…Chronic respiratory failure (as defined by the need of long-term oxygen therapy) occurred in 40% of patients, including four patients who died of respiratory failure [55]. In another series that evaluated 144 patients with rheumatoid arthritis and respiratory manifestations, 5-year survival rates were 36% in 57 patients with usual interstitial pneumonia, 87% in 31 patients with bronchiectasis, 94% in 16 patients with NSIP and 89% in 11 patients with bronchiolitis [83]. It is concluded that bronchiolitis is associated with poor prognosis essentially in patients with severe airflow limitation and marked hyperinflation, and that these features mostly occurred in patients with obliterative (rather than follicular) bronchiolitis.…”
Section: Rheumatoid Arthritismentioning
confidence: 98%
“…This may not be unique to the UIP pattern, as significantly higher numbers of CD4 + T-cells have been described in tissue samples from both UIP and NSIP when compared to purely idiopathic interstitial pneumonia [36]. Distinguishing among patterns of ILD can be useful in prognostication as patients with UIP or DAD have greater 5-year mortality compared to those with patterns such as NSIP or organising pneumonia [37]. …”
Section: Pathologymentioning
confidence: 99%
“…Limited data suggest that a history of smoking is more common among RA patients whose lung biopsy specimens display UIP as opposed to NSIP or other patterns. 41,42 Reasons for this predilection among smokers are unclear. Cigarette smoke extract depletes intracellular glutathione, increases lipid peroxidation, and induces necrosis in human alveolar epithelial cells in a dosedependent manner, 43 suggesting that oxidative stress is a significant trigger for type I pneumocyte loss and alveolar disintegrity.…”
Section: Rheumatoid Arthritis-associated Interstitial Lung Disease: Amentioning
confidence: 99%